Characteristics of Hepatitis C Virus among Intravenous Drug Users in Iceland - Löve, Arthur; Sigurdsson, Jon R.; Stanzeit, Barbara; Briem, Haraldur; Rikardsdottir, Hugrun; Widell, Anders (American Journal of Epidemiology, 1996)
According to antibody analysis, approximately two of every three intravenous drug users in Iceland have become infected with hepatitis C virus (HCV). In this study, serum samples from 55 HCV antibody-positive intravenous drug users (39 males and 16 females) were analyzed by polymerase chain reaction, and the viral strains were grouped into genotypes. Only three genotypes—1a, 3a, and 1b—were found among the drug users. Of 40 persons who were positive by polymerase chain reaction, 23 (57.5%) had type 1a, 15 (37.5%) had type 3a, and one (2.5%) had type 1b. One serum sample was untypeable. HCV viral RNA was detectable in 84.6% of the males and 43.7% of the females, which is a significant difference between the sexes ( p < 0.01). In addition, 41 randomly selected HCV antibody-positive intravenous drug users (17 males and 24 females) were tested for HCV viral RNA with a commercially available polymerase chain reaction technique. In this subset of drug users, 76.4% of the males and 33.3% of the females had detectable HCV RNA in their serum, which is also a significant sex difference (p < 0.01). This study shows that two HCV genotypes predominate among intravenous drug users in Iceland, and the results indicate that women eliminate virus more effectively than men.